An Adiponectin Receptor Agonist Reduces Type 2 Diabetic Periodontitis. (March 2019) - Wu, X.; Qiu, W.; Hu, Z.; Lian, J.; Liu, Y.; Zhu, X.; Tu, M.; Fang, F.; Yu, Y.; Valverde, P.; Tu, Q.; Yu, Y.; et al.
Periodontitis is twice as prevalent in diabetics as in nondiabetics, and type 2 diabetes (T2D)–associated periodontitis is severe in many cases due to the altered and aberrant functions of bone cells in hyperglycemic conditions. Therefore, developing an effective method to halt the disease process, as well as restore and regenerate lost alveolar bone to reserve the natural teeth in diabetics, is critically important. In the current study, we applied a newly discovered adiponectin receptor agonist AdipoRon (APR) in experimental periodontitis in diabetic animal models and demonstrated the underlying molecular mechanisms. We found that when APR systemically quenched the blood sugar level in diet-induced obesity (DIO) diabetic mice, it reduced osteoclast numbers and alveolar bone loss significantly due to APR's inhibition on osteoclast differentiation shown in our in vitro studies. APR also decreased the production of proinflammatory molecules CC chemokine ligand 2 and interleukin 6 in diseased gingival tissues. On the other hand, APR promoted alveolar bone regeneration through enhancing osteogenic differentiation and decreasing stromal cell–derived factor 1 in the bone marrow that facilitates stem cell migration. Same results were achieved by APR treatment of periodontitis induced in adiponectin (APN) knockout mice, indicating the ability of APR to activate the endogenous APN receptors to exert osteoanabolic effects. In summary, our study supports the notion that APR could be used as an effective multipronged approach to target T2D-associated periodontitis.